Penulisan Naskah Film Pendek Komunitas Saba Eksploit SMAN I Bantul, DIY - Wibowo, Ridha Mashudi; Ekasiswanto, Rudi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2022)
The Official Selection World Cinema Amsterdam Award in 2019, given to the film